Rekonstruksi Metode Story telling dalam Pembelajaran Menceritakan Kembali Teks Fabel pada Peserta Didik Kelas VII SMP Al-Hidayah Medan - Wafiq, Chici Al; Haryadi; Setyaningsih, Nas Haryati (Unika Santu Paulus Ruteng, 2024)
Story telling is one method of speaking in the form of telling activities or telling about an event, and is delivered orally which aims to share stories with others and become a method that can be used in fabel’s learning. Retelling the fable text from read or heard is one of the basic competencies that students are expected to be able to do optimally. The purpose of this research is to reconstruct the story telling method with the help of visual aids in class VII SMP Al-Hidayah Medan. This research was conducted by analyzing (1) the conditions of the application of the story telling method (2) the impact of creative teaching aids. The method used in this research is descriptive qualitative method. Data collection techniques in research were conducted by interviews and literature study. The results showed that the application of the method in learning to retell fable texts in grade VII of Al-Hidayah Junior High School still did not get optimal results and responses both in terms of student response, speaking skills, and the absence of media support, so there is a need for reconstruction to achieve better learning outcomes and student responses.